EFFICIENT ORGANIZATION OF THE PROCESS OF SERVICING AUTOMOBILE FLOWS ARRIVING AT THE POINT OF SHIPMENT - Muratov Abobakr Kholikberdievich (Journal Park Publishing, 2023)
This article focuses on the effective organization of the process of servicing automobile flows, as well as improving the efficiency of cargo transportation and reducing the daily unproductive downtime of vehicles. Relevant recommendations are given to improve the performance of gross services and improve the efficiency of work.
Keywords: loading and unloading, automobile, transportation, effective, cargo dispatch point, queue, wait.